Evaluation of Thiol/Disulfide Homeostasis and Neurogenin 3 Levels as a Marker of Oxidative Stress in Children and Adolescents Newly Diagnosed with Type 1 Diabetes - Gözde Deliktaş; Reyhan Deveci Sevim; Tolga Ünüvar (Galenos Publishing House, 2022)
The objective of the study was to determine the relationship between autoimmunity and dynamic thiol/disulfide, neurogenin 3 (ngn 3) status in the newly diagnosed with type 1 diabetes mellitus (T1DM), the level of treatment, and thiol/disulfide homeostasis and neurogenin 3, and to found the changes in neurogenin 3 level due to beta cell damage in children newly diagnosed with T1DM. Totally 60 children aged 1-18 years old, 30 of them newly diagnosed with type 1 diabetes (patients), and 30 of them healthy children in the same age group (control) were included in the study. Insulin and C-peptide levels of newly diagnosed T1DM patients were lower than the control group, however, HbA1c, glucose, creatinine, cholesterol, triglyceride, and LDL levels were found higher in patients. Total thiol level and Gad antibody positive rate were found higher in children newly diagnosed with T1DM. In addition, it was observed that the rate of anti-insulin antibody positivity increased in the 6th-month control of patients. However, HbA1c and glucose levels at diagnosis were higher in patients compared to the control group at the sixth month. Insulin and C-peptide levels were determined lower in patients admitted with diabetic ketoacidosis. A negative correlation was observed between native thiol and anti-insulin antibody parameters and a positive correlation between ngn 3 and total cholesterol and LDL. In conclusion, thiol/disulfide homeostasis and ngn 3 parameters can be used as oxidative stress markers in children and adolescents newly diagnosed with T1DM.